The Role of Islamic Educational Methods on the Cultivation of Religious Awareness in Islamic Psychology - Puspita, Puspita (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2020)
Observation of the conditions and situations of people's lives from the psychological aspect through Islamic education methods has not found satisfaction with religious awareness. In fact, the prophet Muhammad SAW. In guiding and directing the lives of his people, he always emphasizes on psychological factors that are in accordance with the methods and trends of progress in the development of society. This research is inspired by the problems that are now emerging. Related to the problem of the method of Islamic education which in fact conveys the values ​​of akhlakul karimah but the approach does not pay attention to psychological aspects. Therefore, this study will attempt to reveal the role of Islamic education methods in inculcating religious awareness in Islamic psychology. This research is library research through data collection with a variety of literature. The data that has been collected is analyzed using content analysis as an analytical tool so that a variety of views can be found that can complement each other between disciplines that the researcher wants to explore. The results found in this study are Islamic education has a psychological foundation that is Islamic-oriented which is guided by the Qur'an and al-Hadith as its source. So that the end of the purpose of the role of Islamic education methods in instilling religious awareness in Islamic psychology is that it can be realized and create happy human beings in the world and the hereafter. The gap in this research is that regarding the concept of views and the direction of trends in community development, it is necessary to direct the psychological aspects towards the safety of their lives, although the success or failure of the method has not been determined.